“PASSACAGLIA” IN THE OPERA OF THE 20ᵗʰ CENTURY. THE INTERLUDE NO.4 FROM THE OPERA “PETER GRIMES” BY BENJAMIN BRITTEN - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica)
In the assembly of the opera, Passacaglia represents an isle, in the same way in which the isle exists in the sea. Because of the fact that it is situated in the middle of the two scenes of this one, by the central position, it realizes the symmetric cut of the opera. On the podium, we can meet it as an independent work. Musical-dramatic, Passacaglia, by basso ostinato and by the variations which are going on this sound basement, materialized the persistence of the fix idea in the mind of the main character. This studys shows the structural and dramaturgical analysis of this part of the opera entitled Peter Grimes.